The Landau band effects in the quantum magnetic oscillations and the deviations from the quasiclassical Lifshitz-Kosevich theory in quasi-two-dimensional conductors - Gvozdikov, V.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The quantum magnetic oscillations (QMO) in the layered and quasi-two-dimensional (2D) conductors deviatefrom the quasiclassical Lifshitz–Kosevich (LK) theory developed for 3D conventional metals. We discuss deviations related to the broadening of the Landau levels into Landau bands by various mechanisms (layer-stacking,magnetic breakdown, incoherence, disorder, localization etc.). Each mechanism yields a specific factor modulating the QMO amplitudes depending on the density of states and electron velocities within the Landau bands. In contrast to the LK theory, these factors differ for the thermodynamic (de Haas–van Alphen (dHvA)) and kinetic (Shubnikov–de Haas (SdH)) oscillations. We calculated the magnetic breakdown damping factors for the SdH and dHvA oscillations in the 2D conductors and analyzed their difference as well as the analogy between the bandwidth and Weiss oscillations. In case of an isotropic 3D metals the kinetic factors become proportional to the thermodynamic ones as is assumed in the LK theory.